DINAMIKA LOYALITAS KONSUMEN DALAM PEMILIHAN MEREK: STUDI KASUS PADA PEMBELIAN ULANG MOBIL - Sanaji; Indarwati, Tias Andarini (Universitas Nusantara PGRI Kediri, 2016)
Customer loyalty often become a company goal to maintain marketing performance. On the other hand, market situation is dynamic, both in supply and consumers demand, thereby building a truly customer loyalty to the brand is a challenge for marketers. This study used a case study approach to understand how the dynamics of costumer loyalty in brand choice, which is focused on the relation of corporate brand and experience in the use of previous brand when customer repurchase of a new car. The results showed that the corporate brand reputation still be a consideration in selection of new car, but the fit to the need of use a car become key considerations. Of the five cases observed, only one case had consistently choose the same corporate brand, and the rest swicthed to other corporate brand when purchase new car, although the contumers satisfied and not regret on previous brand, and corporate also offers the same product category with the competitors. These findings provide new understanding that in the purchase of products, the suitability of the current needs and the availability of competitors' products are the main driver of brand choice. This study provides a theoretical contributions in understanding the phenomena of loyalty and practical implications for marketers to build brand strategy and new product development.